How to respond to an “accumulated wound”: about memory work in the poetry of Conceição Lima - Amorim, Bernardo Nascimento (2020)
“1953”, a poem from A dolorosa raiz do micondó, by Conceição Lima, approaches the Batepá Massacre, an event that is recorded in the history of São Tomé and Príncipe as a milestone for the imagination of a collective identity, related to the struggle for liberation of the country from colonial rule. It is a traumatic event, whose violence Lima’s poetry works to ensure it will not be forgotten, shedding light on wounds that are part of a national memory. Wounds of a similar nature are also addressed in other poems by the author, such as in the section of O País de Akendenguê entitled “Os fantasmas elementares”. Having in mind the transit between the violence of Batepá and the action of those whose legacy can point ways to the future, I intend to show some of the dialogues that are established in Lima’s poetry, projecting a world with more space for justice and solidarity rather than enmity.